Peran Badan Usaha Milik Desa (BUMDes) Amanah dalam Pengelolaan Wisata Teluk RHU - Ramadhani, Andika Wahyu; Umar, Zulkarnain; Metalisa, Rindi (Fakultas Pertanian Universitas Jember, 2024)
BUMDes Amanah is one of the best BUMDes representing Bengkalis Regency for the Riau Province level. For this reason, research was carried out with the aim of analyzing the roles of institutions and the inhibiting and driving factors in tourism management. The method used in this research is purposive study and determination of respondents. The results of the research are the role of BUMDes as a motivator by providing encouragement such as inviting the community to work together in developing the tourism sector. BUMDes also motivates the community to do something that can develop tourism on the Teluk Rhu coast. The driving and inhibiting factors for BUMDes Amanah have been going quite well but there are still a number of obstacles such as the lack of enthusiasm of the community in participating in developing the tourism sector, the lack of human resources in managing this tourism, inadequate facilities and infrastructure to support aspects of tourism development.